The comparative analysis of the influence of bisoprolol and carvedilol on the course of heart failure of ischemic origin in patients with concomitant atrial fibrillation and diabetes mellitus - N.M. Kulaiets; V.M. Kulaiets (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. The aim of the study was a comparative analysis of bisoprolol and carvedilol effects on the course of heart failure (HF) of ischemic origin in patients with concomitant atrial fibrillation (AF) and diabetes mellitus (DM). Materials and methods. Three hundred and ninety-eight patients with HF on the background of post-infarction cardiosclerosis aged 58 (54–67) years (198 women and 200 men) were examined. Two hundred and twenty-six (56.8 %) had persistent AF, 102 (25.6 %) had concomitant type 2 DM, and 13.1 % had a combination of DM and AF. One hundred and sixty-seven (42.0 %) patients had a reduced left ventricular ejection fraction (LVEF) ≤ 40 %; 133 (33.4 %) had moderately reduced LVEF (41–49 %); 98 (24.6 %) had preserved LVEF (≥ 50 %). The levels of thyroid-stimulating hormone, free triiodothyronine and free thyroxine, glucose, glycated hemoglobin, galectin-3, suppression of tumorigenicity 2 peptide, B-type natriuretic peptide, N-terminal prohormone of brain natriuretic peptide were determined. Genotyping was carried out for 4 polymorphisms (rs1801253 and rs1801252 of the β1-АР, rs1042714 of the β2-AP gene, and rs2274273 of the LGALS-3 gene). ECG registration, daily ECG monitoring, standardized echocardiographic examination during hospitalization were carried out. Two hundred and four (51.3 %) patients took bisoprolol in an individually selected dose for a year; 194 (48 %) patients were prescribed carvedilol. According to this criterion, patients were divided into two groups. During one year, the patients were observed, taking into account the presence of repeated hospitalization (RH) due to HF decompensation. Statistical analysis was performed using the programs Statistica for Windows Release 10.0 and MedCalc® (Statistical Software version 22.020). Results. The frequency of RH was lower by 48.3 % (p = 0.040) in the group of patients with HF with reduced LVEF and AF without DM when using carvedilol, compared to the group that took bisoprolol (odds ratio (OR) = 0.412 [0.158–0.976], p = 0.047). If AF is combined with DM in patients with HF (regardless of phenotype), the frequency of RH when treated with carvedilol is lower compared to the group that took bisoprolol (by 21.1 %; p = 0.0018) (OR = 0.096 [0.010–0.937]; p = 0.044). The frequency of RH was also lower in patients with HF with reduced LVEF, under combined AF and DM, when treated with carvedilol (by 27.3 %; p = 0.027) compared to those who took bisoprolol. According to the probit regression analysis, there was an inverse (β = –0.162 ± 0.034) dependence of the probability of RH in patients with sinus rhythm on the severity of heart rate changes (∆HR) during the year of β-AB use. ROC-analysis showed that in patients with HF with sinus rhythm, the risk of RH increases during the observation period when the optimal distribution point for ∆HR ≤ 15.00 min–1 is reached (sensitivity of 80.30 %, specificity of 68.87 %; p < 0.0001). In HF with AF, a S-shaped (sigmoid) dependence (β = 0.507 ± 0.092) was found of the risk of RH on the severity of heart rate changes against the background of β-AB treatment. At the same time, the risk of RH in HF patients with AF increases upon reaching the optimal distribution point for ∆HR > 22.00 min–1 (sensitivity of 98.12 %, specificity of 87.23 %, p < 0.0001). Conclusions. With the use of carvedilol compared to bisoprolol, the risk of RH is lower in HF patients with AF with reduced LVEF (OR = 0.412, p = 0.047) and in patients with a combination of AF and type 2 diabetes (OR = 0.096, p = 0.044). These drugs have the same effectiveness in patients with sinus rhythm, regardless of the HF phenotype and the presence of concomitant DM. During the titration of the β-AB dose in patients with HF with sinus rhythm, it is advisable to gradually decrease the heart rate > 15 min–1; with AF — no more than 22 min–1.